2023
DOI: 10.1038/s41598-023-29305-5
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-associated lncRNA prognostic signature predicts prognosis and immune response in clear cell renal cell carcinoma

Abstract: Clear cell Renal Cell Carcinoma (ccRCC), the most deadly and life-threatening tumor in the urinary system, has a dismal prognosis and a high risk of metastasizing. Regulation of ferroptosis is a prospective therapeutic target to eradicate malignant cells. Our objective was to seek ferroptosis-associated long non-coding RNAs (FALs) and developed a prediction signature for ccRCC. We extracted transcriptome data and clinical information from The Cancer Genome Atlas (TCGA) databases. Ferroptosis-associated genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In-depth studies have revealed that lncRNAs can either promote or suppress tumours by participating in gene signalling regulation and can serve as promising potential biomarkers [48][49][50]. In a study, eight ferroptosis-associated lncRNAs were used to construct a predictive model that accurately predicted the prognosis of KIRC and suggested treatment options [51]. However, the role of DRlncRNAs in KIRC remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth studies have revealed that lncRNAs can either promote or suppress tumours by participating in gene signalling regulation and can serve as promising potential biomarkers [48][49][50]. In a study, eight ferroptosis-associated lncRNAs were used to construct a predictive model that accurately predicted the prognosis of KIRC and suggested treatment options [51]. However, the role of DRlncRNAs in KIRC remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to existing signatures including several lncRNAs (more than 6) [25,26], our 3-lncRNA model contains the fewer genes and should be easy to apply in the clinic. Different functional lncRNA models, specifically ferroptosis/cuproptosis-associated lncRNA signatures and tumor-infiltrating lymphocyte-related lncRNA models, have been reported to predict ccRCC prognosis [27][28][29]. However, these lncRNAs in models are closely related to immunotherapy and drug response but not to ccRCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, with the in-depth study of a large number of lncRNAs, it was found that lncRNAs can play cancer-promoting or cancer-suppressing roles in a variety of tumors, including KIRC, by participating in gene signaling regulation, and can serve as promising potential biomarkers [46][47][48]. Eight ferroptosisassociated lncRNAs were built into a predictive model that accurately predicted the prognosis of KIRC patients and supplied them with anti-cancer treatment options [49]. However, the role of DRlncRNAs in KIRC remains unknown.…”
Section: Discussionmentioning
confidence: 99%